(Poli) Tickle/Prickle: Keshav Between the Lines. (November 2018) - Venkat, Vishaka; Balakrishnan, Vinod
This interview with Keshav Venkataraghavan, the staff cartoonist of The Hindu, explores the principles and the profession of political cartooning. Known as Keshav, to his readers, he has been drawing for 30 years and is now the editorial consultant of The Hindu . Beginning as a caricaturist who frequented the Chennai concerts to sketch the classical Carnatic musicians, Keshav has metamorphosed into an artist-cartoonist, effortlessly switching between the austere mind devoted to art's spirituality and the specular mind which interrogates the socio-political sphere. While Keshav has drawn attention as an artist, his style of cartooning, surprisingly, has not been examined at length. As this is the first time Keshav becomes candid about the ethics, aesthetics and profession of cartooning, the interview demands attention, especially, for an Indian perception of cartooning. The interview attempts to answer the following questions: What decides the rhetoric, ethics and aesthetics of cartooning? Why is humour significant to cartooning? What is its role in making cartoons controversial? And what distinguishes political correctness from political incorrectness? Beginning with a discussion on the intriguing language of cartooning, the interview ponders over the process of choosing ideas and creating visuals for cartooning. This conversation with Keshav helps one to understand the tightrope profession of cartooning, as a thin separation between the scathed and smooth lines that tickle and prickle targets.